2002
DOI: 10.1089/104454902753759717
|View full text |Cite
|
Sign up to set email alerts
|

Hemopexin: Structure, Function, and Regulation

Abstract: Hemopexin (HPX) is the plasma protein with the highest binding affinity to heme among known proteins. It is mainly expressed in liver, and belongs to acute phase reactants, the synthesis of which is induced after inflammation. Heme is potentially highly toxic because of its ability to intercalate into lipid membrane and to produce hydroxyl radicals. The binding strength between heme and HPX, and the presence of a specific heme-HPX receptor able to catabolize the complex and to induce intracellular antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
299
1
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(310 citation statements)
references
References 68 publications
(55 reference statements)
3
299
1
7
Order By: Relevance
“…Thus, the hemopexin-mediated uptake of heme by the cells has been confused. Finally, hemopexin-deficient mice did not show any impairment of heme metabolism but were sensitive to oxidative stress, as playing a role as anti-oxidants for exogenous insults (Tolosano and Altruda 2002). Along with hemopexin receptors, the presence of heme receptors was reported on the surface of MEL cells, Caco cells and hepatocytes (Uc et al 2004).…”
Section: Transport and Utilization Of Heme In Cellsmentioning
confidence: 97%
“…Thus, the hemopexin-mediated uptake of heme by the cells has been confused. Finally, hemopexin-deficient mice did not show any impairment of heme metabolism but were sensitive to oxidative stress, as playing a role as anti-oxidants for exogenous insults (Tolosano and Altruda 2002). Along with hemopexin receptors, the presence of heme receptors was reported on the surface of MEL cells, Caco cells and hepatocytes (Uc et al 2004).…”
Section: Transport and Utilization Of Heme In Cellsmentioning
confidence: 97%
“…Hemopexin, albumin, a-1-microglobulin, and reduced glutathione are the most well-known heme-binding molecules [15,141]. Hemopexin is an intravascular protein that binds free heme with a very high affinity and protects against heme toxicity in vitro [141][142][143]. This protein protects cells without hemopexin receptors by binding heme and preventing the destructive effects of non-specific heme uptake.…”
Section: The Oxidant Potential Of Heme Is Neutralized By Multiple Hemmentioning
confidence: 99%
“…This protein protects cells without hemopexin receptors by binding heme and preventing the destructive effects of non-specific heme uptake. Hemopexin-heme complexes bind hemopexin receptors, which are taken up by the cell via an endocytotic mechanism [142,144]. Heme is then released from hemopexin into the cell and degraded.…”
Section: The Oxidant Potential Of Heme Is Neutralized By Multiple Hemmentioning
confidence: 99%
“…Hemopexin is critical in maintaining the homeostasis of metal ions by forming a complex with heme. As the major vehicle for the transportation of heme, hemopexin could prevent hememediated oxidative stress and heme-bound iron loss (29), functionally analogous to HO-1, which metabolizes heme and prevent oxidative stress. Taken together, our current study suggested that curcumin could coordinately regulate the phase I, II, and III xenobiotic metabolizing enzyme genes as well as antioxidative stress genes through Nrf2-dependent pathways in vivo.…”
Section: Curcumin and Global Gene Expression Profiles In Micementioning
confidence: 99%